Direct introduction of phosphonate by the surface modification of polymers enhances biocompatibility - Choong, C; Griffiths, J; Moloney, M; Triffitt, J; Swallow, D (2009)
A novel chemical method for the modification of polystyrene and nylon polymers by the reaction of diaryl carbenes permits the direct and efficient introduction of phosphonate residues upon the polymer surface. The method is simple to execute, involving solution coating to adsorb the reactive coating agent, followed by drying and thermolysis at temperatures not greater than 150 °C. This material can be further modified to the calcium phosphonate derivative, by treatment with aqueous calcium hydroxide. The modified polymers show enhanced biocompatibility of the modified polymer, as evidenced by the improved growth of MG63 human osteosarcoma cell line on the surface. This method is of significance since it offers a simple chemical protocol for the tailoring of the surface properties of materials, it avoids the need to construct ab initio new polymers for a given application, it provides an alternative to existing surface modification protocols, and it extends the range of polymers suitable as biocompatible materials . © 2008 Elsevier Ltd. All rights reserved.